2021
DOI: 10.1038/s41598-020-80149-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of nuclear, chloroplast, and mitochondrial genomes of watermelon and melon provides evidence of gene transfer

Abstract: During plant evolution, there is genetic communication between organelle and nuclear genomes. A comparative analysis was performed on the organelle and nuclear genomes of the watermelon and melon. In the watermelon, chloroplast-derived sequences accounted for 7.6% of the total length of the mitochondrial genome. In the melon, chloroplast-derived sequences accounted for approximately 2.73% of the total mitochondrial genome. In watermelon and melon, the chloroplast-derived small-fragment sequences are either a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 44 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…The mitochondrial and nuclear genomes can transfer DNA sequences in both directions. It was reported that a sequence of about 125 kb in the watermelon mitogenome was homologous to a 260 kb sequence in the nuclear genome, accounting for 33% of the mitogenome (Cui et al 2021). Based on relative species, we estimated that there was also a large amount of genetic material has been exchanged among mitochondrial and nuclear genomes of S. tsinyunensis.…”
Section: The Presence Of Mtpts and Mtnusmentioning
confidence: 94%
“…The mitochondrial and nuclear genomes can transfer DNA sequences in both directions. It was reported that a sequence of about 125 kb in the watermelon mitogenome was homologous to a 260 kb sequence in the nuclear genome, accounting for 33% of the mitogenome (Cui et al 2021). Based on relative species, we estimated that there was also a large amount of genetic material has been exchanged among mitochondrial and nuclear genomes of S. tsinyunensis.…”
Section: The Presence Of Mtpts and Mtnusmentioning
confidence: 94%
“…Modernization of the technical and technological base of food industry enterprises using modern types of equipment will increase the depth of processing of agricultural raw materials and thereby reduce their negative impact on the environment, significantly increasing the profitability of production [5].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In plant evolution, migration between plasmid DNA and nuclear DNA was revealed (Blanchard & Schmidt, 1995;Schuster & Brennicke, 1994). Such migration is responsible for the rearrangement of mitochondria and nuclear genomes and for the variants associated with abnormal growth phenotypes (Cui et al, 2021;Gualberto & Newton, 2017;Zhang et al, 2020). We identified the inserted fragments in the…”
Section: Crop Sciencementioning
confidence: 99%